Integrasi Ornamen Aceh dalam Desain Furnitur Minimalis - M. Hamzah; Ichsan Ichsan; Afifuddin Afifuddin; Ahmad Vaza At Thariq; Ikhsan Saputra (Pusat Riset dan Inovasi Nasional, 2025)
Minimalist style, as one of the major streams of modern design, has developed rapidly and influenced various aspects of life, including furniture design in Aceh. Along with the increasing dominance of minimalism, the existence of traditional Acehnese ornamentation has declined in application and tends to stagnate through repetitive use of similar motifs. This study aims to integrate the aesthetic and symbolic values of Acehnese ornamentation into minimalist furniture design through a contextual design approach based on local wisdom. The research applies the Design Thinking method, encompassing stages of contextual exploration, formulation of aesthetic concepts, visual experimentation, and critical reflection. Visual experiments were carried out through manual sketches and digital reproduction using SketchUp, CorelDRAW X7, and Gopain. The study produced two furniture designs a document cabinet and an office desk which combine Acehnese ornaments derived from the tomb complex of Raja Jalil in Lam Lagang and the traditional house of Teungku Chik Awee Geutah in Bireuen. The findings reveal that integrating Acehnese ornamentation into minimalist design can create harmony between tradition and modernity without losing philosophical depth or local identity. The study highlights the significance of a contextual design approach as an innovative strategy for cultural preservation through contemporary furniture creation.